1971
DOI: 10.6028/jres.075a.039
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic mass spectrometric investigation of the reactions of t-C4H9+ ions with some simple polar molecules at thermal energies

Abstract: The int e ra cti o ns of t-C-J-q ions fro m neo pe nta ne with so me s impl e po la r molec ul es have bee n inv es t igate d in a hi gh p ress ure photo io niza ti o n m ass s pec tro me te r at th e rm a l kine ti c e ne rgies. Proton transfe r was fo und to occ ur fro m t-C.Ht to aceto ne . a mm o ni a . a nd th e va ri o us meth y la min es. but not to mo lec ul es hav in g es tim at ed proton affmiti es < 195 kca l/ mol (815 kJ / mol). Mac roscopic th e rm a l rate coe ffi c ie nts a re reported for th e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1973
1973
1977
1977

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
6
1
Order By: Relevance
“…The above observations concerning ion-dipole effects are in contrast to the conclusions reached by Hellner and Sieck (24). They observed that proton-transfer reactions from t-C,H,+ (produced by photoionization of neopentane) to acetone, ammonia, and various methyl amines all had rate coefficients which could be ex~lained by ion-induced dipole interactions only and they concluded that ion-dipole effects were unimportant.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The above observations concerning ion-dipole effects are in contrast to the conclusions reached by Hellner and Sieck (24). They observed that proton-transfer reactions from t-C,H,+ (produced by photoionization of neopentane) to acetone, ammonia, and various methyl amines all had rate coefficients which could be ex~lained by ion-induced dipole interactions only and they concluded that ion-dipole effects were unimportant.…”
Section: Discussioncontrasting
confidence: 55%
“…The thermochemically permitted reactions are1 ' "Thermochemical calculation employs AH,((CH,),-COH+) = 125 kcal mol-' (22,23). A value of 111 kcal mol-I has also been reported (24 Figure 9a shows the variation of ion intensities with time between 0.5 and 2.0 ms in a 157: 1.0 CH4-(CH,),CO mixture where CH5+ is the only reactant ion produced from methane. Figure 9b shows the plot of product ion intensities us.…”
Section: Methane-acetonementioning
confidence: 99%
“…At low CH4 pressures, reaction 14 competes with reaction 13. As the C2H2CI2 pressure is increased, the CH4 •+ intensity decreases via reaction 14 with a resultant decrease in the amount of CHS+ formed via reaction 13. Thus it appears that CHS+ is reacting with C2H2CI2 at a larger rate than the true rate of reaction 15.…”
Section: Methodsmentioning
confidence: 99%
“…The ion cyclotron resonance spectrometer used for the experimental studies is of conventional design and has been discussed in detail elsewhere.1*17 All experiments were carried out at about 300°K. Reactant ions H3+ (or D3+) and CHS+ (or CD5+) were produced by the reactions H,• + + H2-> H3+ + • H ( 12) and CH4-+ + CH4 -CHs+ + • CH3 (13) 30-eV electrons were used to form the methane and hydrogen ions. Thermal energy rate constants were measured by observing the decrease of reactant ion intensity at constant methane or hydrogen pressure while increasing the target gas pressure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation